Controlling the Polarity of the Molecular Beam Epitaxy Grown In-Bi Atomic Film on the Si(111) Surface - Lin, Cho-Ying (Sci Rep, 2019)
Synchrotron radiation core-level photoemission spectroscopy, scanning tunneling microscopy (STM), and first-principles calculations have been utilized to explore the growth processes and the atomic structure of the resulting films during the two-step molecular beam epitaxy (MBE) of In and Bi on the Si(111) surface. Deposition of 1.0-ML Bi on the In/Si(111)-(4 × 1) surface at room temperature results in Bi-terminated BiIn-(4 × 3) structures, which are stable up to ~300 °C annealing. By contrast, deposition of In on the β-Bi/Si(111)-(√3 × √3) surface at room temperature results in three dimensional (3D) In islands. In both cases, annealing at 460 °C results in the same In-terminated In(0.75)Bi/Si(111)-(2 × 2) surface. Our DFT calculations confirm that the surface energy of In-terminated In(0.75)Bi/Si(111)-(2 × 2) system is lower than that of Bi-terminated Bi(0.75)In/Si(111)-(2 × 2). These findings provide means for the control of the polarity of the MBE In-Bi atomically thick films.